História de vida docente na intersecção com o processo de aquisição da leitura e escrita no 1º ciclo do ensino fundamental - SANTOS, Arcilene Chaves dos (2019)
The present research is the report of my experiences as a teacher of the 1st cycle of Elementary School. It is configured as a autobibliographic study that makes a resumption of the schooling process, intertwining situations relevant to the teaching career. It aims to verify how the literacy process appears in the life history of a teacher of the 1st cycle of Elementary School in the municipality of Santa Maria do Pará and is structured in IV sections: in the first, an introduction is presented with the justification and the objective of the research. The second section outlines the research paths. The third section presents the National Pact for Literacy in the Right Age as a training policy at the intersection with my teacher's life history in the first cycle of the initial grades. The fourth and last section brings the narrative of the entrance and experience in the pedagogy course. It was evidenced that the lived and shared experiences were primordial for professional formation and had a direct repercussion on my teaching practice.